QISHLOQ XO’JALIGI MAHSULOTLARINI ISHLAB CHIQARISHNING MAMLAKATIMIZ IQTISODIYOTIGA TA’SIRI (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article discusses that Crotalaria (Crotalaria juncea) plant is planted at the rate of 14 kg per hectare in the conditions of the meadow gray soils of the Jizzakh region, along with the planting of Geogumat biostimulator at the rate of 1.0 l/t and 1.6 l/ha in 3-4 true leaving and branching periods, dry weight of the plant is 94.56 g, 2.42 g of the control variant; Geohumat biostimulant 2.11 g from the variant was used only with planting; It was stated that the biostimulant of grapes was up to 1.22 g more than the variant used only with planting.